2005
DOI: 10.1093/nar/gki626
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring tat peptide binding to TAR RNA by solid-state 31P-19F REDOR NMR

Abstract: Complexes of the HIV transactivation response element (TAR) RNA with the viral regulatory protein tat are of special interest due in particular to the plasticity of the RNA at this binding site and to the potential for therapeutic targeting of the interaction. We performed REDOR solid-state NMR experiments on lyophilized samples of a 29 nt HIV-1 TAR construct to measure conformational changes in the tat-binding site concomitant with binding of a short peptide comprising the residues of the tat basic binding do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
75
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(75 citation statements)
references
References 55 publications
0
75
0
Order By: Relevance
“…Previous work has demonstrated that phosphorothioate and 2′-fluorine substitutions at those positions do not perturb the structure of TAR26-28. These labels were added to allow us to verify the conformation of TAR RNA using REDOR methods28.…”
Section: Methodsmentioning
confidence: 99%
“…Previous work has demonstrated that phosphorothioate and 2′-fluorine substitutions at those positions do not perturb the structure of TAR26-28. These labels were added to allow us to verify the conformation of TAR RNA using REDOR methods28.…”
Section: Methodsmentioning
confidence: 99%
“…Here, we describe a combination of RNA-labeling techniques as well as NMR methods and applications to a well-established model system, the human immunodeficiency virus (HIV) transactivation response element (TAR) (Fischer et al, 1996;Fischer, Gdaniec, Olejniczak, Bielecki, & Adamiak, 1999;Hennig et al, 2006Hennig et al, , 2007Huang, Varani, & Drobny, 2010; Olejniczak et al, 2002;Olsen et al, 2005;Scott et al, 2004). The Tat (transcription activator)-TAR complex formation provides an essential gene regulatory function for HIV (Marciniak, Calnan, Frankel, & Sharp, 1990;Seelamgari et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The labeling did not affect the RNA structure or function and allowed the determination of the valine-tRNA recognition sites of the cognate aminoacyl-tRNA synthetase by 19 F-NMR spectroscopy. Since then, 2 0 F-labeled nucleotides have become widely used in solid-state and liquid-state NMR spectroscopy (Kreutz et al 2005;Olsen et al 2005). The modification on the ribosyl moiety of nucleotides allows the use of one similar labeling schema for all nucleobases.…”
Section: Introductionmentioning
confidence: 99%